Effects of Surface Curvature and Surface Strength on Argon Adsorption in Carbon Nanotubes at Temperatures below the Triple Point - Zhongjun Liu; D.D. Do; D. Nicholson; Zhengping Xi (Adsorption Science & Technology)
This paper describes an investigation of argon adsorption into carbon nanotubes at temperatures below the triple point, using a grand canonical Monte Carlo simulation to study the effects of confinement and surface strength on the 2D transition. In large pores, it was found that 2D transitions can occur in more than one layer, but are absent in higher layers for small pores. The 2D critical temperature of the first layer for a small pore (R = 1.2 nm) was found to be ca. 66 K (MWCNT) and 65 K (SWCNT), compared to 55–59 K observed experimentally for a flat graphite surface. This is because of the overlapping effects due to the surface curvature or the confinement in a carbon nanotube. Assuming a weaker carbon surface by reducing the graphene surface strength by 40% for SWCNT, the 2D critical temperature was only modestly reduced to 63 K. This suggests that the experimental data at 59 K might be attributed to other factors, other than confinement effects. An imperfect surface is suggested and, employing 5% defects on this surface, the 2D critical temperature has been determined as 58 K which is in better agreement with the experimental value of 59 K.